2010
DOI: 10.1177/1934578x1000500927
|View full text |Cite
|
Sign up to set email alerts
|

Terpene Bioconversion – How does its Future Look?

Abstract: The usage of essential oils as such or of volatile fractions thereof is widespread in the flavor and fragrance industry to aromatize perfumery and cosmetic products, foodstuffs, and many household and pharmaceutical products. The increased market share of convenience food together with consumers' request for constant high quality and natural products have established a lasting increase in the demand for natural flavorings that cannot be satisfied by the traditional plant materials. This review summarizes selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 122 publications
0
26
0
Order By: Relevance
“…This has also been important for testing our understanding for biochemical processes in general and understanding the genetic and biochemical components associated with terpene biosynthetic enzymes (Mandel et al 1996). Second, generating transgenic plants accumulating altered amounts of a specific terpene or suite of terpenes can be evaluated for their health-promoting properties (Sawai and Saito 2011) or could provide new means for the sustainable production of high-value chemicals for industrial uses (Krings and Berger 2010). …”
Section: Introductionmentioning
confidence: 99%
“…This has also been important for testing our understanding for biochemical processes in general and understanding the genetic and biochemical components associated with terpene biosynthetic enzymes (Mandel et al 1996). Second, generating transgenic plants accumulating altered amounts of a specific terpene or suite of terpenes can be evaluated for their health-promoting properties (Sawai and Saito 2011) or could provide new means for the sustainable production of high-value chemicals for industrial uses (Krings and Berger 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Park et al [19] also found that LAB signi cantly reduced the terpene content of blueberry juice, including a 92% reduction in vitispirane. The causes of terpene reduction were not fully known, but could involve oxidation to secondary products, glycoside hydrolysis, or ester conversion, as well as isomerization and / or interconversion of some monoterpenols [13,[23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Belviso et al [26] found that LAB cultures can completely degrade alpha-campholenal and form a new monoterpenoid in 48 hours. Although terpenes are formally composed of one biosynthetic unit, the fact that they can be biotransformed by mechanisms including hydration, isomerization, dehydrogenation, conjugation, oxidation, reduction, decarboxylation, and β-oxidation, means that multiple structures can be produced [2,13]. Microorganisms that promote the biological transformation of terpenes include bacteria, fungi, and yeast.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pleurotus species offer a number of additional technical advantages, i.e. sequenced genome, short life cycle, easy cultivation in solid and liquid media, and first biotechnological applications have become known (Cohen et al, 2002;Krings and Berger, 2010). In Pleurotus species, the mating system is controlled by two unlinked mat loci, A and B (bifactorial).…”
Section: Introductionmentioning
confidence: 97%